PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KESEHATAN PADA RUMAH SAKIT PANTI SECANTI GISTING - Emilia Widiati (JMBA Jurnal Manajemen dan Bisnis, 2015)
To be able to implement the Hospital health efforts are efficient and effective by giving priority to curative and rehabilitative efforts are conducted in a harmonious and integrated with promotive and preventive efforts and to implement the Human Resource references in it are required to have good performance. Likewise with the Children's Hospital Secanti. For that investigated employee performance Secanti Hospital Panti, Gisting, in this study examined factors that influence the performance of Children's Hospital Secanti, Gisting is a factor of work motivation, work discipline and organizational culture. Data analysis techniques used in this study is a descriptive technique is the analysis by way of expressing or describing the circumstances or the accurate facts from the observed object, in accordance with the prevailing theory. This study used sampling methods, namely how to perform sampling of the population is known, either from the method of determining the number of samples and sampling of the model in question, with the expectation that the sample used to represent populsinya. determination of the number of samples in this study using proportionate stratified random sampling method, namely the determination of a random sample in the lower position. The data used are primary data collected through questionnaires and secondary data gathered through library research. These data were analyzed through correlation analysis, determination koofisien test, regression test and t test for hypothesis testing. Furthermore, the conclusion: there were positive and significant influence between motivation Work (X1) on employee performance (Y) with a correlation of test results for 0874, presenting the relationship of 76.4%, for Work Discipline relations (X2) to variable (Y) for 0675 , presentation of the relationship by 45.6% is also positive and significant effect, whereas the relationship Cultural Organization (X3) with variable (Y) for 0869, presenting the relationship of 75.6% also had a positive and significant impact on the performance of Children's Hospital employees Secanti , Gisting. Thus note that the quality of HR (Human Resources) at the Hospital Panti Secanti, Gisting quite good and very strong views of the three variables: Work Motivation, Discipline of Work and Organizational Culture together / simultaneously with the correlation 0927, presentation by 86 ties, 0%. Based on the results of hypothesis tests obtained probability (Sig. = 0.000 a) <0.05 (α) then H0 rejected and H1 accepted or there is significant influence between motivation, work discipline and organizational culture on employee performance Secanti Children's Hospital.